高中職普通生霸凌行為之研究 The Bullying Behavior Study of Regular Students in Senior High and Vocational High Schools - 林慧敏 Huei-Min Lin; 黃開成 Kai-Cheng Huang; 蔡田木 Tyan-Muh Tsai (National Taiwan Normal University, 2024)
校園霸凌對學生身心傷害至鉅，是學校長期面臨的棘手問題。本研究引用日常活動論，對桃竹地區2,171位高中職普通生探討校園霸凌情形，探究普通生霸凌行為的路徑，並驗證霸凌經驗、受凌經驗對霸凌行為的影響。所得結果如下：首先，根據桃竹地區高中職普通生的霸凌行為調查，得到自陳霸凌者8.6%與國內校園霸凌相關調查結果相似。經迴歸分析後發現，普通生的霸凌行為主要受性別、族群、父親教育的影響，只是背景對霸凌行為的解釋力不高；但加入中介變項如學校、身心因素及霸凌經驗、受凌經驗後，整體模型對霸凌行為的解釋力便大幅提升。其次，影響霸凌行為的路徑可分為二：一是男生霸凌較女生高，男生對霸凌有直接正向影響外，還會間接透過同學欺負較高、自信較高對霸凌有正影響。二為漢人學生霸凌較原住民學生低，漢人學生對霸凌有直接負向影響外，還會間接透過中介變項對霸凌行為產生影響；在間接影響上，漢人學生知覺學校因應較低，霸凌會較高，不過，漢人學生的自信較低，霸凌也較低，因此整體而言漢人學生的霸凌行為仍較低。本研究證實普通生的霸凌經驗會提高霸凌他人的行為，受凌經驗也會增加霸凌他人的行為。最後，根據研究結果提出校園霸凌防制的具體建議。 Motivation and Purpose School bullying has adverse effects on students' physical health and is closely related to criminal behavior in adulthood, which may pose a threat to society. Although bullying behavior peaks in elementary, secondary, and high school, studies focusing on bullying among ordinary students in senior high schools and vocational high schools are limited. Therefore, the present study investigated the prevalence of bullying among ordinary students in senior high schools and vocational high schools and the factors that contribute to their bullying behavior. The study elucidated the landscape of bullying among students in senior high schools and vocational high schools and the pathways leading to bullying behavior in these students. Specifically, the study explored whether experiences of bullying and being bullied increase the likelihood of subsequent bullying behavior. The research deviated from the convention of using qualitative interviews or a consultation-based approach in Taiwanese studies on the topic by employing a quantitative methodology. Moreover, this study investigated the impacts of bullying experiences and victimization experiences on bullying behaviors. The study applied routine activity theory (RAT) to analyze data collected from 2,171 students from senior high schools and vocational high schools to elucidate the pathways and effects associated with bullying behaviors. Literature Review The research findings revealed that demographic variables, such as gender, ethnicity, grade level, family socioeconomic status, and school features, as well as personal experiences of bullying and being bullied had an impact on bullying behavior. Additionally, three factors that contribute to bullying behavior were identified: family-related factors, including parenting style, family atmosphere, and family support; school-related factors, such as classroom atmosphere, teacher-student interactions, peer interactions, school responses to bullying, and academic performance; and physical and psychological factors, such as sports participation, self-identity, and empathy. These family-related factors, school-related factors, and physical and psychological factors were used as mediating variables in an analysis of the pathways leading to bullying among ordinary students. Methodology The mediating variables were measured using a questionnaire that was primarily developed with reference to the scales or studies of other scholars, with the items from several scales being modified and compiled. Before the official questionnaire was administered, a pilot test analysis involving 808 students from high schools and vocational high schools from areas outside the Taoyuan and Hsinchu counties was conducted. Inappropriate items were removed or modified on the basis of the pilot test results to ensure the reliability and validity of the questionnaire. Subsequently, a formal questionnaire survey was conducted with regular high school and vocational high school students in the Taoyuan and Hsinchu counties, with an effective sample size of 2,171 participants. This study aimed to elucidate the prevalence of campus bullying. Percentage and mean analyses and F tests were conducted on the background variables and bullying behaviors. Multiple regression analysis was performed on bullying behaviors to explore the influencing pathways. Additionally, the impact of experiences of bullying and being bullied on bullying behavior was examined. Final Results The study revealed three key findings. First, the regression analysis indicated that the explanatory power of the general students' bullying behavior with respect to background was not high. However, when mediating variables such as school, physical and psychological factors, and experiences of bullying and being bullied were introduced, the explanatory power of the overall model for bullying behavior was considerably higher. Second, the study identified pathways through which independent variables influenced the dependent variable through mediating variables. For instance, male students exhibited a higher level of bullying than female students did, and the positive impact of gender on bullying among male students was both direct and indirect. The indirect effect was mediated by a higher number of experiences of bullying from classmates and stronger self-identity, with both of these factors contributing positively to bullying behaviors. In addition, the Han Chinese students exhibited lower levels of bullying than the Indigenous students did. The direct negative impact of being Han Chinese on bullying was also indirectly mediated by intermediate variables influencing bullying behavior; the Han Chinese students perceived lower levels of school responsiveness to bullying incidents, leading to higher levels of bullying. However, the Han Chinese students had lower self-identity, which led them to exhibit less bullying behavior than the Indigenous students did. Third, the study confirmed that experiences of bullying or being bullied among regular students increased the likelihood of engaging in bullying behavior. Discussion and Recommendations This study revealed that bullying by peers has a positive effect on subsequent bullying behavior, and a school's response to bullying has a negative effect on bullying. According to RAT, experiencing more bullying from classmates leads individuals to develop an inclination to engage in bullying in their daily lives. This aligns with the general characteristics of aggressors of possessing both the ability and motivation to bully. In addition, the results revealed that students perceiving their school to effectively respond to bullying indicates inefficient monitoring by the school to curb bullying, that is, indicates a lack of supervision to prevent such incidents. The interplay of these two factors creates an environment that enables aggressors to exploit others. Characteristics such as vulnerability, unattractiveness, unpopularity, past experiences of rejection by peers, and a lack of friends make an individual susceptible to bullying. On the basis of these findings and drawing from the RAT framework, we offer two key recommendations for preventing bullying. First, schools can reduce bullying by implementing long-term, continual, antibullying advocacy activities in the school; strengthening campus safety monitoring systems; and developing comprehensive bullying prevention training programs. Second, opportunities for bullies to engage in such behavior can be reduced through interventions and counseling by experts and teachers, which can reduce the likelihood of bullying incidents. Additionally, victims can participate in social skills training programs organized by teachers.